PENGARUH PRAKTIK PENGALAMAN LAPANGAN TERHADAP KOMPETENSI PEDAGOGIK MAHASISWA PPG PRAJABATAN BIDANG STUDI PENDIDIKAN PANCASILA UNIVERSITAS RIAU - Aisyah Zoelpa, Sabrina; Hambali; Radini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education plays a strategic role in developing knowledgeable and character-driven human resources, making teacher quality a key determinant of learning success. However, pedagogical competence among teachers remains a challenge, particularly in understanding student characteristics, designing instruction, and conducting effective evaluation. The Pre-service Teacher Professional Education (PPG Prajabatan) program addresses this issue through Field Experience Practice (PPL), which integrates theoretical knowledge with real classroom practice. This study aims to examine the effect of Field Experience Practice on the pedagogical competence of pre-service PPG students majoring in Pancasila Education at the University of Riau. This research employed a causal associative survey method involving 21 students who participated in the PPL program in the 2024 Batch II. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed using simple linear regression with SPSS. The results indicate that Field Experience Practice has a positive and significant effect on students’ pedagogical competence, demonstrating that direct teaching experience contributes substantially to the development of professional teaching skills.